The Great Indian Epics : The Stories of the Ramayana and the Mahabharata - Oman, John Campbell (Brill | Manohar Publishers & Distributors, 2024)
This title is a concise version of the English translation of Mahabharata and Ramayana. Since Ramayana and Mahabharata are the lengthiest epics written in the history of India, only select themes of both Epics have been covered by the author, which are of great importance. This is a preliminary version of two major Sanskrit works for familiarization with the Indian literature and religion.